2020
DOI: 10.1101/2020.04.23.041509
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stroma secreted IL6 selects for “stem-like” population and alters pancreatic tumor microenvironment by reprogramming metabolic pathways

Abstract: Pancreatic adenocarcinoma is a devastating disease with an abysmal survival rate of 9%. A robust fibro-inflammatory and desmoplastic stroma, characteristic of pancreatic cancer, contributes to the challenges in developing viable therapeutic strategies in this disease. Apart from constricting blood vessels and preventing efficient drug delivery to the tumor, the stroma also contributes to aggressive biology of the cancer along with its immune-evasive microenvironment. In this study, we show that in pancreatic t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…However, many cancer patients do not respond initially or develop secondary resistance. In their review, Cerezo and Rocchi 2 discuss how targeting metabolism could help modulate antitumor immunity and exploring the possibility that the metabolic reprogramming in cancer cells may represent a way to favor the antitumor response 7 . Another key factor in the development of cancer tumor resistance to therapy is discussed in the review by Dong et al 3 highlighting the contribution of exosomes to drug resistance in breast cancer.…”
Section: Years Of Cell Death and Diseasementioning
confidence: 99%
“…However, many cancer patients do not respond initially or develop secondary resistance. In their review, Cerezo and Rocchi 2 discuss how targeting metabolism could help modulate antitumor immunity and exploring the possibility that the metabolic reprogramming in cancer cells may represent a way to favor the antitumor response 7 . Another key factor in the development of cancer tumor resistance to therapy is discussed in the review by Dong et al 3 highlighting the contribution of exosomes to drug resistance in breast cancer.…”
Section: Years Of Cell Death and Diseasementioning
confidence: 99%
“…11 Furthermore, data acquired from several solid tumors shows that tumor immunometabolic reprogramming is highly essential, which will continue to be a new emphasis of COAD research in the future. [12][13][14] Fatty acids are essential for energy storage, membrane synthesis, and signaling molecule production during oncogenesis. 15 It has been shown that decoding the molecular mechanism of COAD and fatty acid metabolism might aid in the identification of new therapeutic targets and the development of successful treatment techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The disruption of lipid metabolism, specifically for fatty acid metabolism with altered expression and activity of lipid‐metabolizing enzymes as a result of abnormal activation of oncogenic signaling pathways, has been widely recognized as a critical factor of metabolic reconfiguration within cancer cells and immune cells that may lead to the long‐term development of COAD 11 . Furthermore, data acquired from several solid tumors shows that tumor immunometabolic reprogramming is highly essential, which will continue to be a new emphasis of COAD research in the future 12–14 . Fatty acids are essential for energy storage, membrane synthesis, and signaling molecule production during oncogenesis 15 .…”
Section: Introductionmentioning
confidence: 99%